Forecasting the gross domestic product (GDP) of Sarawak - Tan, Chiou Sia (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This study intends to examine the detenninant of Gross Domestic Product (GDP) of Sarawak and use them to forecast the GDP of Sarawak. The empirical test that is used in this study includes unit root test and 10hansen-luselius cointegration test. The models that are employed are Autoregressive Integrated Moving Average (ARlMA), Vector Error Correction (VEC) model, and fundamental model. The results state that exports has strong relationship with GDP. The results also indicate that Vector Error Correction (VEC) model produces the highest forecast accuracy for full sample and in-sample forecast whereas fundamental model produces the highest forecast accuracy for out-sample forecast.